Trade Sanctions — Effects and Side Effects - Thieß Petersen; Thomas Schwab (Wirtschaftsdienst)
Abstract Trade sanctions have been repeatedly used as an instrument to force countries to change policies or actions that are considered condemnable. Trade sanctions put pressure on a country by purposefully harming its economy. The resulting economic costs are intended to translate into political costs for the government of the target country. In this article, we outline the economic mechanisms behind trade sanctions and resulting effects for both the implementer and the target country. We also discuss the implications of our findings in light of the current sanction regime against Russia.